2011
DOI: 10.1111/j.1478-5153.2011.00464.x
|View full text |Cite
|
Sign up to set email alerts
|

Critical care outreach referrals: a mixed‐method investigative study of outcomes and experiences

Abstract: Mapping outreach episodes of care and patient outcomes can help highlight areas for improvement. This study outlines reasons for referral and how outreach can facilitate patient pathways in critical illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
88
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(90 citation statements)
references
References 35 publications
(51 reference statements)
0
88
0
2
Order By: Relevance
“…These assessment skills are developed by nurses from knowing the patient and from past experiences which were based on subjective rather than objective criteria (Cioffi 2000b, Mackintosh et al2012. As a result findings suggest that experienced nurses use a complex interaction of intuition, protocols and clinical judgment to recognise patient deterioration and not just the objective MET criteria to refer patients (Pattison &Eastham 2011, Johnston et al 2014. As a result EWS were used flexibly by senior staff to support decision making (Pattison & Eastham 2011, Mackintosh et al 2012, Hands et al 2013.…”
Section: Clinical Judgement (Mechanism)mentioning
confidence: 99%
See 3 more Smart Citations
“…These assessment skills are developed by nurses from knowing the patient and from past experiences which were based on subjective rather than objective criteria (Cioffi 2000b, Mackintosh et al2012. As a result findings suggest that experienced nurses use a complex interaction of intuition, protocols and clinical judgment to recognise patient deterioration and not just the objective MET criteria to refer patients (Pattison &Eastham 2011, Johnston et al 2014. As a result EWS were used flexibly by senior staff to support decision making (Pattison & Eastham 2011, Mackintosh et al 2012, Hands et al 2013.…”
Section: Clinical Judgement (Mechanism)mentioning
confidence: 99%
“…Critical care experience in particular was found to improve nurses' knowledge and recognition of deteriorating patients (Thompson et al 2009, Pattison & Eastham 2011. Findings concluded that engagement in deliberate practice is the primary means by which nurses attain expertise (Whyte et al 2009) and that the experience of staff may be fundamental in reducing risk (Wheatley 2006).…”
Section: Experience (Mechanism)mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous data showed that 30% of emergency critical care referrals result in the patient being admitted to a critical care unit, with the remainder of the patients either achieving stable condition in a general care area, improving in condition, or being transferred to EOL care. 6 In this study, we also planned to assess longterm mortality outcomes of these EOL patients, as previous data have indicated that EOL patients who are sick enough to be referred to outreach do poorly in 100-day and 6-month outcome data, even if they survived the hospital and/or critical care episode. …”
mentioning
confidence: 99%